Synchrotron Radiation Pair Distribution Function Analysis of Gels in Cements - Cuesta-García, Ana María; Zea-Garcia, Jesus D.; Londono-Zuluaga, Diana; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel; Vallcorba, Oriol; García-Aranda, Miguel Ángel (MDPI, 2017)
The analysis of atomic ordering in a nanocrystalline phase with small particle sizes, below 5 nm, is intrinsically complicated because of the lack of long-range order. Furthermore, the presence of additional crystalline phase(s) may exacerbate the problem, as is the case in cement pastes. Here, we use the synchrotron pair distribution function (PDF) chiefly to characterize the local atomic order of the nanocrystalline phases, gels, in cement pastes. We have used a multi r-range analysis approach, where the ~4–7 nm r-range allows determining the crystalline phase contents; the ~1–2.5 nm r-range is used to characterize the atomic ordering in the nanocrystalline component; and the ~0.2–1.0 nm r-range gives insights about additional amorphous components. Specifically, we have prepared four alite pastes with variable water contents, and the analyses showed that a defective tobermorite, Ca11Si9O28(OH)2 8.5H2O, gave the best fit. Furthermore, the PDF analyses suggest that the calcium silicate hydrate gel is composed of this tobermorite and amorphous calcium hydroxide. Finally, this approach has been used to study alternative cements. The hydration of monocalcium aluminate and ye’elimite pastes yield aluminum hydroxide gels. PDF analyses show that these gels are constituted of nanocrystalline gibbsite, and the particle size can be as small as 2.5 nm
Keywords: Cemento Portland; Portland cement; C-S-H gel; Cementitious materials; Amorphous phases; Total scattering